Perhitungan Struktur Atas Gedung Bertingkat pada Pembangunan Kantor Dinas Tenaga Kerja dan Transmigrasi Jl.AP.Pranoto KecamatanTenggarong, Provinsi Kalimantan Timur - ROSIT, ALI (KURVA S JURNAL MAHASISWA, 2013)
A Structure planning process is a direct, detail, repeat, and coherent process accordingto function, layout, utility of the building. In the implementation in the field occurred severaltimes reposition, based on the layout of the building will influent condition of the building structure plan.The Location of concrete office building development activities of labor and transmigration District of Tenggarong in East Kalimantan. Data are collected in a secondary way of the data, it is required to support primary data from related literature, and the primary data collected in field.The content of this thesis is to known the structure portal calcutated from reinforce concrete and another included structure elements with mechanic calculation on a convensional based on Takabeya method, planning and component structure analysis reinforce concrete based on SNI 03-2847-2002.The result from the researcher’s calculated finding the structure reinforce concre tecalculation will be completed with Takabeya method, because it more practice than another classic methods. And while design reinforce concrete process used the biggest moment value from observed result calculating of every single reinforce concrete with Takabeya method and for the structure reinforce concrete result calculating it exist a little differences on reinforce concrete structure design like as in main beam dimension and reinforcement total used.